Eyelid Opening with Trigeminal Proprioceptive Activation Regulates a Brainstem Arousal Mechanism - Matsuo, Kiyoshi (PLoS One, 2015)
Eyelid opening stretches mechanoreceptors in the supratarsal Müller muscle to activate the proprioceptive fiber supplied by the trigeminal mesencephalic nucleus. This proprioception induces reflex contractions of the slow-twitch fibers in the levator palpebrae superioris and frontalis muscles to sustain eyelid and eyebrow positions against gravity. The cell bodies of the trigeminal proprioceptive neurons in the mesencephalon potentially make gap-junctional connections with the locus coeruleus neurons. The locus coeruleus is implicated in arousal and autonomic function. Due to the relationship between arousal, ventromedial prefrontal cortex, and skin conductance, we assessed whether upgaze with trigeminal proprioceptive evocation activates sympathetically innervated sweat glands and the ventromedial prefrontal cortex. Specifically, we examined whether 60° upgaze induces palmar sweating and hemodynamic changes in the prefrontal cortex in 16 subjects. Sweating was monitored using a thumb-mounted perspiration meter, and prefrontal cortex activity was measured with 45-channel, functional near-infrared spectroscopy (fNIRS) and 2-channel NIRS at Fp1 and Fp2. In 16 subjects, palmar sweating was induced by upgaze and decreased in response to downgaze. Upgaze activated the ventromedial prefrontal cortex with an accumulation of integrated concentration changes in deoxyhemoglobin, oxyhemoglobin, and total hemoglobin levels in 12 subjects. Upgaze phasically and degree-dependently increased deoxyhemoglobin level at Fp1 and Fp2, whereas downgaze phasically decreased it in 16 subjects. Unilateral anesthetization of mechanoreceptors in the supratarsal Müller muscle used to significantly reduce trigeminal proprioceptive evocation ipsilaterally impaired the increased deoxyhemoglobin level by 60° upgaze at Fp1 or Fp2 in 6 subjects. We concluded that upgaze with strong trigeminal proprioceptive evocation was sufficient to phasically activate sympathetically innervated sweat glands and appeared to induce rapid oxygen consumption in the ventromedial prefrontal cortex and to rapidly produce deoxyhemoglobin to regulate physiological arousal. Thus, eyelid opening with trigeminal proprioceptive evocation may activate the ventromedial prefrontal cortex via the mesencephalic trigeminal nucleus and locus coeruleus.